O gênero exposição oral: descrição e análise de sua aplicação no contexto do ensino médio - Félix, Regina Lúcia (2009)
As a Portuguese language teaching professional, we have noticed the difficulty of High School students in using oral language appropriately in different formal communicative events which they are exposed to. Due to this fact, we have become interested in analyzing how the oral mode of the Portuguese language, in its standard school register, has been developed in High School. In order to elaborate this study, we have begun with the hypothesis that oral genres are not formally addressed in the educational context, especially in High School, since teachers do not have a theoretical and pedagogical approach to support their practice. If (and when) this occurs, there is no previous planning for its execution. Because of the variety and scope of oral genres in the school space, we have narrowly defined as a goal for this research to describe and analyze the application of oral presentations in the context of High School in two state high schools from the city of Patrocínio, state of Minas Gerais. Based on the collected corpus, we describe and analyze: (a) the conditions for production in which the students presentations occurred; (b) the internal construction of the presentations performed by them; (c) the mechanisms of textual articulation which are present in their oral production and (d) some non-verbal communication elements which are judged relevant for the understanding of the genre. The corpus was collected during two months, and is comprised of five presentations given in classes of Portuguese (Literature), Biology, Geography and Physics. The study was based principally on the theoretical perspective of Schneuwly & Dolz et al. (2004), Rojo (2000, 2001, 2002, 2005, 2007) and Marcuschi (1999, 2001, 2002, 2003, 2005). We have found in our analysis that the genre oral presentation is not formally addressed in the classroom referring to form, probably because teachers regard verbosity only as a vehicle to conduct language. For these teachers, tasks with oral presentation had as a focus mainly content transmission. We have also verified that tasks with the oral modality of language are conducted with frequency in the classroom, but without pedagogical interventions related to the way in which students perform their oral presentations. When it comes to the teachers, we have noticed, through semi-structured interviews, that the majority are not aware of and view as new the possibility of teaching discursive genres. In this regard, they lack theoretical and pedagogical foundation. Nevertheless, they acknowledge this deficiency and are willing to welcome the application of the genre oral exposition as a new practice with their students. Therefore, this study may contribute not only for the teachers to recognize the relevance of oral presentation in the educational context and in the students social life, but also for them to develop a systematic set of tasks in the classroom, which may enable teachers to competently employ this genre in the several situations of formal communication.